Circular Dichroism Second-Harmonic Generation Imaging of KTiOPO4 Nanocrystal Through Stratified Media - Wu, Biwei; Wu, Keyi; Sun, Xuefeng; Wang, Weibo; Tan, Jiubin (Frontiers in Chemistry, 2022)
Potassium titanyl phosphate (KTiOPO4, KTP) particle of nanometric size (nano-KTP) is an attractive material for nonlinear microscopy, and the optimized growth of large-size KTP single crystals has numerous applications for efficient frequency conversion in laser technology. Its three-dimensional orientation and nanoscale morphology are important for growth optimization. In this paper, we introduce an imaging technique based on circular dichroism second-harmonic generation (CD-SHG) to characterize the 3D distribution of KTP nanocrystal. A rigorous theoretical model of CD-SHG imaging for nano-KTP through stratified media is demonstrated. Circular dichroism analysis is used to probe the orientation of 3-axis with respect to the optical observation axis. The research results show that the azimuthal angle of the peak value (SHG) or valley value (CD-SHG) is strongly related to the excitation polarization when the KTP sample is excited by different circular polarizations. Importantly, the refractive index mismatches and the imaging depth also affect the azimuthal angle. Thus, the proposed framework enables a more precise quantitative analysis of the CD-SHG signal of KTP.